Hukum yang Diperjualbelikan Jual Beli Putusan dalam Etika Profesi Hakim di Pengadilan - Sulistiawati; Endah Ratnawati; Siti Nur Ambarini; Muh Arbai Santoso; Iyus YL Tobing; Firman Adi Candra (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Law is a fundamental instrument in creating order and justice within society. In its implementation, the law should be applied objectively, independently, and free from any form of intervention. However, in judicial practice, deviations are often found in the form of the practice of trading court decisions, which undermines the principle of justice. This phenomenon not only damages the integrity of the judiciary but also weakens public trust in the legal system. This article aims to examine the ethics of the judicial profession as the main pillar of law enforcement, reveal legal facts related to the practice of trading court decisions in the courts, and explain the patterns and background of this practice. Furthermore, the article discusses the negative impacts caused and effective strategies to eradicate the practice of trading court decisions in order to uphold the supremacy of a fair and clean rule of law. This writing is expected to contribute to promoting judicial reform and increasing awareness of the importance of integrity within the judiciary profession.